Motivations for remittances: Evidence from Moldova - Matloob Piracha; Amrita Saraogi (University of Kent, School of Economics, 2011)
This paper explores the factors that account for the receipt of remittances across households in Moldova who have migrant family members abroad. Unlike most of the existing literature, we approach our research question from the perspective of the recipient household and use it to interpret the determinants/motivations of remittances. Our results show that a combination of household and migrant characteristics and some community level variables are the key elements in explaining the remittance behaviour in Moldova. Drawing from these estimates, we conclude that altruism and investment (proxied by the level of economic development at the regional level) are the two main motives behind remittance flows to Moldova.
Keywords: F22; F24; 330; remittances; migration; Moldova; Rücküberweisung (Migranten); Motivation; Migranten; Moldawien